Kasus Fidelis Ditangkap dan Ditahan atas Kepemilikan Batang Ganja untuk Pengobatan Sang Istri Ditinjau dari Aliran Realisme Hukum - Syahrial; Maya Intan Pratiwi; Rian Prayudi (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Legal realism is a school that does not agree with the existence of precedents (the existence of ties between a judge's decision and previous judge's decisions in dealing with similar issues). And understanding legal realism views the law as an advocate views the law. For an advocate, the most important thing in looking at the law is how to predict the outcome of a legal process and what the future holds for these legal rules. The school of legal realism actually hopes for the role of judges in realizing justice, so that in certain cases judges do not always adhere to the provisions contained in legislation only (rule-responsive), they also need to look at the situation that actually occurs in practice (fact-responsive). In this case, it seems that the judge took into account the existence of legal realism by assessing the facts that prompted Fidelis to commit a crime (possessing 39 marijuana stalks) for the treatment of his wife, so the judge imposed a sentence on Fidelis that was far from the minimum threat. And criticism of the school of legal realism was also raised regarding matters relating to its views on the judicial process. In this case, criticism is raised against the Normative statement and the concept of "logic", whereas the realist emphasis is only on difficult cases. Keywords: Ownership of Marijuana Stems, Treatment of the Wife, Legal Realism